Behavior, kinetic and product characteristics of the pyrolysis of oil shale catalyzed by cobalt-montmorillonite catalyst. (1st June 2020) - Jiang, Haifeng; Hong, Wenpeng; Zhang, Yu; Deng, Sunhua; Chen, Jie; Yang, Chen; Ding, Haoshu
Highlights: Coupling effect advanced the thermal decomposition of organic matters in oil shale. A significant coupling effect was achieved at the MMT/CoCl2 ·6H2 O mass ratio of 5:1. MMT and CoCl2 ·6H2 O promoted decarboxylation and free-radical reaction of pyrolysis. Coupling effect significantly promoted the formation of saturated hydrocarbons. Abstract: In this work, the effects of the coupling between montmorillonite and CoCl2 ·6H2 O on pyrolysis behavior, products distribution and characteristics of liquid fuel were investigated by the combination of pyrolysis experiment and kinetic analysis. The mass fraction of the MMT in oil shale was 3–9%, and the mass fraction of CoCl2 ·6H2 O was 10–25%. The results showed that the coupling effect promoted the formation of shale oil. The maximum yield of shale oil (17.75 wt%) was obtained at 20CoCl2 ·6H2 O5MMT. Catalytic pyrolysis behavior and kinetic analysis indicated that the presence of CoCl2 ·6H2 O and montmorillonite led to the prominent advance of kerogen decomposition temperature and the decrease of apparent activation energy. Significantly, the addition of the 20CoCl2 ·6H2 O5MMT led that the average apparent activation energy was decreased by about 122.42 kJ/mol compared to the catalyst-free pyrolysis. The strong cracking ability produced by their coupling effect was considered to be the main reason. Montmorillonite and CoCl2 ·6H2 O enhanced the decarboxylation and free-radical reaction, resulting in a decrease of acids yield and an increase of aliphatic hydrocarbons yield. The relative content of aliphatic hydrocarbons increased from 41.55% to 51.27%. These results demonstrated that the combined use of montmorillonite and CoCl2 ·6H2 O was beneficial to the generation of saturated hydrocarbon production.